Two component dark matter with inert Higgs doublet: neutrino mass, high scale validity and collider searches - Subhaditya Bhattacharya; Purusottam Ghosh; Abhijit Kumar Saha; Arunansu Sil (Journal of High Energy Physics, 2020)
Abstract The idea of this work is to investigate the constraints on the dark matter (DM) allowed parameter space from high scale validity (absolute stability of Higgs vacuum and perturbativity) in presence of multi particle dark sector and heavy right handed neutrinos to address correct neutrino mass. We illustrate a simple two component DM model, consisting of one inert SU(2) L scalar doublet and a scalar singlet, both stabilised by additional Z 2 × Z 2 ′ $$ {\mathcal{Z}}_2× {\mathcal{Z}}_2^{′ } $$ symmetry, which also aid to vacuum stability. We demonstrate DM-DM interaction helps achieving a large allowed parameter space for both the DM components by evading direct search bound. High scale validity puts further constraints on the model, for example, on the mass splitting between the charged and neutral component of inert doublet, which has important implication to its leptonic signature(s) at the Large Hadron Collider (LHC).